Onion Farmer Income and Rural Ec Pendapatan Petani Bawang dan Perkembangan Ekonomi Pedesaan Nagari Sirukam - Irvan, Muhammad; Harahap, Erni Febrina (Universitas Dharma Andalas, 2025)
Abstract Agriculture is an economic sector that plays an important role in supporting the sustainability of human life, because farmers are the main actors in providing food and guaranteeing national food security. However, farmers' income is often not commensurate with the hard work and risks they face. Meanwhile, the results from the agricultural sector can also be used as industrial raw materials and a source of food, which makes this sector increasingly important, covering social, economic, environmental and institutional components and is expected to become a driver of economic sectors in rural economic development. The problem in this research is analyzing the onion farmers' income from the variables of price, labor, production and land area. The data used is primary data taken from 33 onion farmers from 4 jorong in Nagari Sirukam. The method used is multiple regression analysis. Temporary research results show that prices and production results have a positive and significant effect on onion farmers' income, meaning that if prices rise and production results increase, then onion farmers' income will increase. However, labor and land area are not significant. Keywords: onion farmer income, price, land area, rural economic development Abstrak Pertanian merupakan salah satu sektor ekonomi yang berperan penting dalam mendukung keberlanjutan kehidupan manusia, dikarenakan petani sebagai pelaku utama dalam menyediakan bahan pangan dan penjamin ketahanan pangan nasional. Namun pendapatan petani sering sekali tidak sebanding dengan kerja keras dan risiko yang mereka hadapi. Sementara hasil dari sektor pertanian dapat juga dimanfaatkan sebagai bahan baku industri dan sumber bahan pangan yang menjadikan sektor ini semakin penting yang mencakup komponen sosial, ekonomi, lingkungan dan kelembagaan dan diharapkan menjadi penggerak sektor-sektor ekonomi dalam pembangunan ekonomi pedesaan. Masalah dalam penelitian ini menganalisis pendapatan petani bawang dari variable harga, tenaga kerja, produksi dan luas lahan. Data yang digunakan adalah data primer yang diambil dari 33 petani bawang dari 4 jorong di Nagari Sirukam. Metode yang digunakan adalah analisis Data Panel. Hasil penelitian sementara menunjukkan harga dan hasil produksi berpengaruh positif dan signifikan terhadap pendapatan petani bawang, artinya jika harga naik dan hasil produksi naik, maka pendapatan petani bawang akan meningkat. Namun tenaga kerja dan luas lahan tidak signifikan. Keywords : pendapatan petani bawang, harga, luas lahan, pembangunan ekonomi pedesaan